Neotropical Anacardiaceae (cashew family) - John D. Mitchell; Susan K. Pell; Julien B. Bachelier; Emily J. Warschefsky; Elizabeth M. Joyce; Laura Calvillo Canadell; Cíntia Luíza da Silva-Luz; Clement Coiffard (Brazilian Journal of Botany, 2022)
Anacardiaceae is an ecologically and economically important plant family of about 200 species in 32 genera in the Neotropics. The family is particularly diverse in leaf architecture and fruit morphology, making it a model family to study the evolution of structural diversity as it correlates with lineage diversification. This fruit diversity is the primary reason 11 of the Neotropical genera are monotypic and that so many genera are recognized in the Anacardiaceae. The economic value of the family is driven by the global markets for cashews, mangoes, and pistachios, but there is great potential value in its medicinal properties. At least 10 Neotropical genera cause contact dermatitis, which is a rich area for research in the family. Here presented is a review of the systematics and structural diversity of the family. Particular attention is given to the morphology, economic botany, paleobotany, ecology, and taxonomy of native and naturalized genera. Keys to Neotropical Anacardiaceae subfamilies and genera are provided along with descriptions of native genera.